2020
DOI: 10.1093/jpp/rgaa019
|View full text |Cite
|
Sign up to set email alerts
|

Zanthoxylum zanthoxyloides inhibits lipopolysaccharide- and synthetic hemozoin-induced neuroinflammation in BV-2 microglia: roles of NF-κB transcription factor and NLRP3 inflammasome activation

Abstract: Objectives The effects of a root extract of Zanthoxylum zanthoxyloides on neuroinflammation in BV-2 microglia stimulated with LPS and hemozoin were investigated. Methods ELISA, enzyme immunoassay and Griess assay were used to evaluate levels of cytokines, PGE2 and NO in culture supernatants, respectively. Microglia-mediated neurotoxicity was evaluated using a BV-2 microglia-HT-22 neuron transwell co-culture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…There have been suggestions in scienti c literature that malaria hemozoin activates NLRP3 in ammasome/caspase-1 pathway to release IL-1β (Dostert et al 2009;Shio et al 2009;Velagapudi et al 2019;Ogunrinade et al 2021). In this study, we have demonstrated signi cant inhibition of hemozoininduced NLRP3 protein expression by all plants investigated.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…There have been suggestions in scienti c literature that malaria hemozoin activates NLRP3 in ammasome/caspase-1 pathway to release IL-1β (Dostert et al 2009;Shio et al 2009;Velagapudi et al 2019;Ogunrinade et al 2021). In this study, we have demonstrated signi cant inhibition of hemozoininduced NLRP3 protein expression by all plants investigated.…”
Section: Discussionsupporting
confidence: 50%
“…Recently, we reported that an extract of Zanthoxylum zanthoxyloides attenuated neuroin ammation induced with synthetic hemozoin in BV-2 microglia (Ogunrinade et al 2021). These reports are encouraging developments, and suggest that further pharmacological evaluation of plants used in TAM for treating malaria and/or CM is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…As a downstream factor of TLR4/MyD88/IRAK, NF-κB also shows a pivotal role in inflammation meditated by microglia. Blockade of NF-κB transcription in the microglial nucleus leads to the downregulation of NO, PGE2, and related proinflammatory cytokines [37][38][39]. In the cytoplasm, phosphorylation of IκBα results in its further ubiquitination and degradation, and consequently, NF-κB dimers are released and translocated to the nucleus to activate the expression of target genes [40].…”
Section: Discussionmentioning
confidence: 99%
“…Skimmianine {4, 7, 8-Trimethoxyfuro [2, 3-b] quinoline} ( Figure 1 ) is the most abundant furoquinoline alkaloid found in the Zanthoxylum genus, and also in other genera of the family Rutaceae [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%